Detection of polymyxin-resistant Enterobacteriaceae from poultry farms in Brazil: continued mcr gene dissemination - Bruno Rocha Pribul; Kathelyn Soares dos Santos; Ramon Pimenta; Orlando Carlos da Conceição-Neto; Ana Paula D’Alincourt Carvalho-Assef; Miliane Moreira Soares de Souza; Cláudio Marcos Rocha-de-Souza (Brazilian Journal of Microbiology, 2026)
The emergence and persistence of plasmid-mediated polymyxin resistance in Brazilian poultry production pose a significant One Health challenge. Here, cloacal swabs from 202 broilers across four farms in the State of Rio de Janeiro yielded 125 Enterobacteriaceae isolates growing on polymyxin-EMB agar. Escherichia coli accounted for 99% of resistant isolates, with one Klebsiella pneumoniae . Multidrug resistance (MDR) was observed in 75% of polymyxin-resistant strains. PCR screening revealed mcr-1 and mcr-5 genes. Conjugation assays demonstrated horizontal transfer of mcr-1 plasmids (48.5–194 kb). MLST assigned key strains to ST10 and ST48, both within the high-risk CC10 lineage. These findings underscore the entrenched nature of polymyxin resistance despite regulatory bans, highlight the risk of zoonotic transmission of MDR determinants, and call for enhanced surveillance, biosecurity and alternative interventions to mitigate the spread of mobile polymyxin resistance in poultry environments.

Inventory Review of the Geological Heritage of the Territory of the Serra Do Sincorá Geopark Project, Bahia, Brazil - Ramon Borges Nolasco Oliveira; Ricardo Galeno Fraga de Araújo Pereira; Renato Pimenta Azevedo (Geoheritage, 2026)
This study presents an updated inventory of the geological heritage at the territory of the proposed Serra do Sincorá Geopark, located in Chapada Diamantina, Bahia, Brazil. The area covers 6,313 km² across the municipalities of Andaraí, Lençóis, Mucugê, and Palmeiras. It includes much of the Chapada Diamantina National Park (PARNA-CD), a major tourist destination in Brazil. Situated within the Espinhaço Supergroup, the region is notable for its rich geodiversity, primarily composed of sedimentary rocks from the Proterozoic Eon, affected by low-grade metamorphism and of significant scientific, educational, and touristic relevance. The study involved literature review, fieldwork, and the evaluation of 45 geological sites: 22 from the original proposal, 9 identified by other authors (Fanha 2019; Parra forthcoming), and 14 newly proposed sites. These new inventoried sites emphasize geotourism, a key pillar of the Geopark concept. Field visits during 2024 enabled site descriptions, followed by inventory using the GEOSSIT application from the Geological Survey of Brazil (SGB/CPRM), which assessed scientific, educational, touristic value, and degradation risk. The results underscore the international significance of iconic sites at the territory, such as Cachoeira da Fumaça and Morro do Pai Inácio. New geosites like Cachoeira do Sossego, Cachoeira do Herculano, and Pedreira do Capão were classified with national relevance. The study strengthens the Serra do Sincorá Geopark proposal, contributing to its future application to the UNESCO Global Geoparks Network and promoting geoconservation, environmental education, and sustainable development through geotourism.

Poultry slaughterhouse wastewater as a driver of bacterial community shifts and the spread of antibiotic resistance genes in aquatic ecosystems - Beatriz Oliveira de Farias; Eliene dos Santos Lopes; Barbara Costa Pereira; Ramon Loureiro Pimenta; Cláudio Ernesto Taveira Parente; Lucy Seldin; Enrico Mendes Saggioro (Environmental Monitoring and Assessment, 2025)

Degradation of plasmid-mediated resistance genes in poultry slaughterhouse wastewater employing a UV/H2O2 process: A metagenomic approach - Beatriz Oliveira de Farias; Enrico Mendes Saggioro; Kaylanne S. Montenegro; Mariana Magaldi; Hugo Sérgio Oliveira Santos; Ramon Loureiro Pimenta; Kayo Bianco; Maysa Mandetta Clementino (Chemosphere, 2025)

Poultry slaughterhouse wastewater as a source of bacterial antimicrobial resistance - Juliana Ferreira Nunes; Thereza Cristina da Costa Patricio; Beatriz Oliveira de Farias; Hosana Dau Ferreira de Souza; Ramon Loureiro Pimenta; Maysa Beatriz Mandetta Clementino; Miliane Moreira Soares de Souza; Irene da Silva Coelho; Shana de Mattos de Oliveira Coelho (Brazilian Journal of Microbiology, 2024)

Metagenomic insights into plasmid-mediated antimicrobial resistance in poultry slaughterhouse wastewater: antibiotics occurrence and genetic markers - Beatriz Oliveira de Farias; Enrico Mendes Saggioro; Kaylanne S. Montenegro; Mariana Magaldi; Hugo Sérgio Oliveira Santos; Andressa Silva Gonçalves-Brito; Ramon Loureiro Pimenta; Rosana Gomes Ferreira; Bernardete Ferraz Spisso; Mararlene Ulberg Pereira; Kayo Bianco; Maysa Mandetta Clementino (Environmental Science and Pollution Research, 2024)